Dopamine‐Integrated Nanointerface between Fibrillar Matrix and Hydrophilic Nanohydroxyapatite Regulates Immune Microenvironment to Boost Endogenous Bone Regeneration (Adv. Funct. Mater. 16/2023). (18th April 2023) - Li, Xing; Li, Zhulian; Wang, Peilei; Lu, Gonggong; Tong, Lei; Liu, Quanying; Chen, Yafang; Lin, Jiangli; Luo, En; Liang, Jie; Jiang, Qing; Fan, Yujiang; et al.
Abstract : Bone Regeneration In article number 2212738, Yong Sun and co‐workers construct a hybrid interwoven scaffold by nano‐sized interfacial integration between fibrillar matrix and hydrophilic nanohydroxyapatite, which recreated a suitable immune microenvironment and drove functional cell/cytokine adhesion to initiate robust vasculogenesis and osteogenesis.